2015
DOI: 10.5721/eujrs20154822
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of three algorithms for the operational estimation of [CHL] from MODIS data in the Western Mediterranean Sea

Abstract: Three algorithms based on MODIS imagery were evaluated for the estimation of Chlorophyll-a concentration ([CHL]) in the Western Mediterranean Sea. The first algorithm (OC3M) is usually applied at global scale, while the second (MedOC3), has been used in the Mediterranean basin. The third algorithm (SAM_LT), specifically developed for the Ligurian and North Tyrrhenian Seas, is here described and applied, in its updated version. The three algorithms were assessed through comparison with 240 sea [CHL] samples col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…Although planktonic productivity in the region has been relatively well addressed, there have been major challenges in the field, particularly regarding the optical properties of the water column, which are essential for phytoplankton growth and productivity. As phytoplankton are the primary source of the marine food chain, they also control the carbon dioxide uptake by the ocean known as the biological pump and, then play a role in the global carbon cycle (Pieri et al 2015). Evaluating the optical properties of the water column thus plays a key role in determine and understand variations in the fluxes of carbon and associated biogenic elements in the ocean (Platt & Sathyendranath 1988).…”
Section: Introductionmentioning
confidence: 99%
“…Although planktonic productivity in the region has been relatively well addressed, there have been major challenges in the field, particularly regarding the optical properties of the water column, which are essential for phytoplankton growth and productivity. As phytoplankton are the primary source of the marine food chain, they also control the carbon dioxide uptake by the ocean known as the biological pump and, then play a role in the global carbon cycle (Pieri et al 2015). Evaluating the optical properties of the water column thus plays a key role in determine and understand variations in the fluxes of carbon and associated biogenic elements in the ocean (Platt & Sathyendranath 1988).…”
Section: Introductionmentioning
confidence: 99%
“…No in-situ measurements were available in the coastal areas of the AB. Nevertheless, Pieri et al, (2015) have found that the OC3M standard algorithm (used in our work) gives valid results in the Western Mediterranean Sea when the Chl-a concentration does not exceed 1 mg m -3 . In our case, the Chl-a exceeds 1 mg m -3 generally in the three first kilometers from coast (i.e.…”
mentioning
confidence: 68%
“…Previous studies using Chl-a variability as a proxy of the phytoplankton biomass variability along the Algerian basin have focused on large spatial scales, mainly over the continental shelf (Mayot et al, 2016;Pieri et al, 2015;Salgado-Hernanz et al, 2019). They have generally ignored small scales and coastal waters, except locally for sanitary purposes or risk assessment.…”
Section: Sources Of Coastal Enrichmentmentioning
confidence: 99%
“…When a pixel from a MODIS L2 image was flagged, it was masked by LAND and CLDICE. HILT was flagged if any of the bands or detectors reaches physical saturation, whereas STRAY-LIGHT showed the brightness of adjacent pixels on a pixel's reflectance value [21]. After this, maps for each month for both SST and Chla were generated using Matlab [17].…”
Section: Methodsmentioning
confidence: 99%